Analisis Ketercapaian Penerapan Kebijakan RPP Satu Lembar Dalam Proses Pembelajaran Di SMA Negeri 12 Buru : Analisis Ketercapaian Penerapan Kebijakan RPP Satu Lembar Dalam Proses Pembelajaran Di SMA Negeri 12 Buru - Tri Kurnia Badu; Vivi Rahim Hentihu; Siti Hajar Loilatu; Suraya Mukadar (LP. Ma'arif Janggan Magetan, 2022)
The purpose of this study in general is to find out how the application of one sheet lesson plan in SMA Negeri 12 Buru is, how is the suitability of the substance in the one sheet lesson plan to the achievement of the learning system, what factors support and hinder teachers in implementing the one sheet lesson plan policy, what are the solutions taken to overcome the problems that arise in the application of the one sheet lesson plan policy at SMA Negeri 12 Buru. Meanwhile, the specific objectives of this study are to describe the application of one sheet lesson plan at SMA Negeri 12 Buru, to analyze the suitability of the substance in the lesson plan one sheet to the achievement of the teaching system at SMA Negeri 12 Buru, to find out the factors that support and hinder the implementation of the single sheet lesson plan policy. at SMA Negeri 12 Buru and understand the solutions taken to overcome the problems that arise in implementing the one sheet lesson plan policy at SMA Negeri 12 Buru. Based on the results of research found by researchers in the field, it was found that the implementation of 1 sheet of lesson plans at SMA Negeri 12 Buru had been running effectively and efficiently. The achievement of the learning process during the pandemic period tends to decrease substantially, but with the application of one sheet lesson plan at SMA Negeri 12 Buru, it can help teachers to meet learning targets, through distance learning that is short, clear and concise so that learning materials are delivered properly where grades are good. students have passed the predetermined standard (KKM). In addition, teachers make various efforts to train their abilities in teaching and compiling and implementing one sheet lesson plans, both through trainings and webinars.